Agua del suelo y aereación en la producción de frijol rojo. 1 Succión máxima media de humedad del suelo - Forsythe, W.M; Legarda B, L (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
Grain and aerial dry matter production and the number of pods per plant were found to be maximum in the '27-R' cultivar of Phaseolus vulgaris L, a red bean grown in the tropics, when the maximum soil moisture suction was 0.8 bars at 5 cm depth or 0.6 bars at 15 cm depth. The experiment was carried out in 26 liter pots of fumigated soil in a greenhouse at CATIE, Turrialba, Costa Rica, with plant spacing similar to field conditions. When the maximum suctions were greater or lesser than the optimum yield value, there was a reduction in yield. It was found that grain production loss per unit bar of suction change when the cyclic maximum suctions were less than the optimum value, were 15 times greater than the rate of production loss when the values were greater than the optimum. No disease nor pest problems were encountered during the study. Potential evapotranspiration increased to a maximum at the eight week and subsequently decreased. Evapotranspiration decreased with increasing maximum suction.